Psychological Aspects of Glaucoma. Issue 3 (March 2016) - Jeong, Ah Reum; Kim, Chan Yun; Kang, Min Hee; Kim, Na Rae
Abstract : Abstract: Glaucoma is a group of optic neuropathies that is more prevalent among the elderly population and commonly associates with comorbidities, including mental disorders in that population. This article reviews the relationship between glaucoma and mental disorders. In it, we discuss the coexistence of glaucoma and mental illnesses, including Alzheimer's disease, depression, and personality disorder. We also focus on the proper treatment approaches for glaucoma patients with mental comorbidity and poor treatment adherence. We summarize some cautiously recommended psychotherapeutic medications, while also discussing the psychologically adverse effects of antiglaucoma medications.